Fluorescence and confocal laser scanning microscopy imaging of elastic fibers in hematoxylin-eosin stained sections - deCarvalho, H. F.; Taboga, SR (Springer, 1996)
We have studied the possibility of associating fluorescence microscopy and hematoxylin-eosin staining for the identification of elastic fibers in elastin-rich tissues. Elastic fibers and elastic laminae were consistently identified by the proposed procedure, which revealed itself to be easy and useful for the determination of such structures and their distribution. The fluorescence properties of stained elastic fibers are due to eosin staining as revealed by fluorescence analysis of the dye in solution, with no or only minor contribution by the elastin autofluorescence. The main advantage of this technique resides in the possibility of studying the distribution of elastic fibers in file material without further sectioning and staining. The use of the confocal laser scanning microscope greatly improved the resolution and selectivity of imaging elastic fibers in different tissues. The determination of the three-dimensional distribution and structure of elastic fiber and laminae using the confocal laser scanning microscope was evaluated and also produced excellent results.